1977
DOI: 10.1136/gut.18.11.865
|View full text |Cite
|
Sign up to set email alerts
|

Unstirred layer and kinetics of electrogenic glucose absorption in the human jejunum in situ

Abstract: SUMMARY Using an electrical technique we estimated the thickness of the unstirred layer in the human jejunum during kinetic studies of electrogenic glucose absorption. The unstirred layer in seven healthy volunteers (632 + 24 ,um: mean + SEM) was significantly thicker than in 10 patients with active coeliac disease (442 + 23 ,um) but not significantly different in seven patients who had responded to treatment by gluten withdrawal (585 + 49 ,um). There were similar differences in the values of 'Apparent Km' for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The firmly adherent mucus layer has been indicated as 107-155 and >200 µm (Forstner et al 1995;Gustafsson et al 2012;Huh et al 2003;Johansson 2014;Kerss et al 1982;Pullan et al 1994). Jejunum mucus in humans had a thickness of 632 µm as assessed by in vivo measurements (Read et al 1977), and the average thickness of the mucus layer in the oral cavity varied between 70 and 100 µm (Collins and Dawes 1987) (Fig. 1).…”
Section: Oral Routementioning
confidence: 99%
“…The firmly adherent mucus layer has been indicated as 107-155 and >200 µm (Forstner et al 1995;Gustafsson et al 2012;Huh et al 2003;Johansson 2014;Kerss et al 1982;Pullan et al 1994). Jejunum mucus in humans had a thickness of 632 µm as assessed by in vivo measurements (Read et al 1977), and the average thickness of the mucus layer in the oral cavity varied between 70 and 100 µm (Collins and Dawes 1987) (Fig. 1).…”
Section: Oral Routementioning
confidence: 99%
“…Previous attempts to measure the thickness of an unstirred layer in the human jejunum used several different techniques, and reported thicknesses have ranged from 600 m (11,12) to 40 m (13). As discussed above, the observed hydrolysis of low concentrations of maltose in the rat could not have occurred if the unstirred layer over the villous tips had been thicker than ‫ف‬ 20 m. Analysis of the absorption of low glucose concentrations in man indicated that the observed absorption rates could not have occurred if the unstirred layer were greater than 40-m thick (13).…”
Section: Discussionmentioning
confidence: 99%
“…Not long after, many pharmaceutical scientists began using computer modeling to model biopharmaceutical and pharmacokinetic processes (Beckett and Tucker, 1968), including the kinetics of buccal absorption (Beckett and Pickup, 1975), as well as to solve intractable or difficult pharmacokinetic analysis of advanced models for oral absorption (Wagner, 1975). Later analyses included computer modeling of transport processes across human gastrointestinal epithelia, including the presence of an aqueous diffusion layer and saturable transport in the human jejunum (Read et al, 1977) and numerical simulation of differential equations describing absorption processes along the length of the intestine (Atkins, 1980). The principles applied in these studies then evolved to include digital computing and deconvolution methodology to assess gastric and intestinal absorption (Veng-Pedersen, 1987).…”
Section: In Silico Modelingmentioning
confidence: 99%